Kajian Macam Pola Tanam Jajar Legowo dan Kombinasi Pupuk Terhadap Pertumbuhan dan Produksi Tanaman Padi (Oryza sativa L.) - Muhammad Usman; Choirul Anam; Mariyatul Qibtiyah; Istiqomah Istiqomah (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2019)
This research was conducted in Botoputih Village, Tikung District, Lamongan Regency. Altitude of ± 6 Masl. Research in February - April 2019. Using Factorial Randomized Block Design (RBD) method, which consists of two factors each factor consists of 3 levels which are repeated 3 times, i.e. : Jajar Legowo cropping factor (J) consists of 3 treatments, namely : Jajar Legowo 2:1 cropping pattern (J1), Jajar Legowo 3:1 cropping pattern (J2), Jajar Legowo 4:1 cropping pattern (J4). The fertilizer combination factor (P) consists of 3 treatments, namely : fertilizer combination of Petroganik 500 kg. ha-1 + PHONSKA 300 kg. ha-1 + Urea 200 kg. ha-1 (P1), fertilizer combination of Petroganik 500 kg. ha-1 + Urea 300 kg. ha-1 + SP-36 75 kg. ha-1 + KCl 50 kg. ha-1 (P2), fertilizer combination of Petroganik 500 kg. ha-1 + ZA 300 kg. ha-1 + SP-36 75 kg. ha-1 + KCl 50 kg. ha-1 (P3). The parameters observed included: tall plants, number of tillers, number of productive tillers, panicle length, number of grain per panicle, weight of wet grain per sample, weight of dry grain per sample, weight of dry grain per hectare and weight of 1000 seeds. Data from observations are calculated by analysis of variance followed by a 5% Least Significance Different (LSD) Test. This study aims to determine the effect of the treatment of legowo jajar cropping patterns and the best combination of fertilizers on rice growth and production. Treatments that provide high productivity are J1P3 (Jajar Legowo 2:1 cropping pattern and fertilizer combination of of Petroganik 500 kg ha-1 + ZA 300 kg. ha-1 + SP-36 75 kg. ha-1 + KCl 50 kg. ha-1)